Status Hara (Rasio C/N dan C/P), Derajat Infeksi Akar dan Bobot Kering Tanaman Jagung (Zea mays) Akibat Perlakuan Inokulasi Mikoriza dan Aplikasi Kompos pada Inceptisol Jatinangor - Pujawati Suryatmana; Leoni Silvia; Mieke Rochimi Setiawati; Emma Trinurani Sofyan; Nadia Nuraniya Kamluddin; Betty Natalie Fitriatin (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2023)
The status of nutrients N, P, and soil organic content in corn cultivation is an important thing that needs to be pursued to improve soil quality. One such effort is through mycorrhizal inoculation and the application of appropriate compost. The aim of this study was to evaluate the effectiveness of arbuscular mycorrhizal fungi (FMA-1) and compost types on soil chemical properties (C/N, C/P), degree of root infection, and corn pruning weight (Zea mays) on Inceptisols. The experiment used three replications of a factorial randomized block design (RBD). The first factor of FMA inoculation: FMA 0 gpot-1, FMA-1 20 g/pot; Mycofer 20 g/pot, and mix (FMA-1 10 g/pot + FMA mycofer 10 g/pot), and the second factor is compost application: 0 g/pot; 75 gpot-1 rabbit hutch compost; 75 g/pot market waste compost and rabbit cage compost 37.5 g/pot + market waste compost 37.5 g/pot). The results showed that there was no interaction between AMF inoculation and the application of compost which affected soil chemical properties, degree of root infection, and dry weight of corn plants. However, independently AMF affects the degree of root infection, and compost affects the dry weight of corn plants. A dose of 20 g/pot FMA and mixed FMA inoculation (FMA and Mycofer) significantly increased the degree of root infection compared to the control treatment. The application of all types of compost showed a significant increase in corn plant dry weight compared to the control. Doses of 75 g/pot of market waste compost tended to increase plant dry weight higher than other treatments with an addition of 32.07 g each plant.